ASSESSMENT OF MEDICATION KNOWLEDGE, MEDICATION ADHERENCE AND HEALTH RELATED QUALITY OF LIFE (HRQoL) AMONG OUT PATIENTS IN TERTIARY CARE CARDIAC HOSPITAL - Mohamed Thayub S; Lydia Jeris W; RajGanesh R; Jaya Shree D; Raveena P B; Kotturathu Mammen Cherian (Journal of Biomedical and Pharmaceutical Research, 2020)
Background: Cardiovascular disease (CVD) is the leading cause of mortality in India. Adherence to medication has been shown to reduce mortality and rate of hospital readmissions. Medication adherence as well as patient’s medication knowledge is also an important factor in validation and management of chronic illness. HRQoL indicates patient’s perceptions of their general, physical, mental health status and describes health burden in a population. Hence the aim of this was to assess the level of medication adherence, barrier to medication compliance, association between knowledge about medication and medication adherence and health related quality of life among CVD patients.Methods: A prospective observational study was conducted for a period3 months. Interview questionnaires for socio-demographic and clinical characteristics as well as the HRQoL, medication adherence, medication knowledge were used to collect data from 211 patients from the cardiovascular unit of Frontier Lifeline Hospital.Result: Of the study population 59% were male and had a mean age of 58 years.  The majority of participants (53%) were taking more than five medications. 34% of the study population had low adherence towards medication intake. The physical component of HRQOoL revealed that 28% of the participants had low scores in physical functioning, bodily pain and general health domains.Conclusion: Medication adherence may be a surrogate marker of Health Related Quality of Life among patients and hence health care providers should identify patients with poor medication adherence and monitor their medication use.Keywords: Medication Adherence, HRQoL , Medication Knowledge , Cardiovascular Patients